2017
DOI: 10.1021/acssynbio.6b00297
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Combinatorial Codon Mutagenesis Method for Targeted Protein Engineering

Abstract: Directed evolution is a powerful tool for optimizing enzymes, and mutagenesis methods that improve enzyme library quality can significantly expedite the evolution process. Here, we report a simple method for targeted combinatorial codon mutagenesis (CCM). To demonstrate the utility of this method for protein engineering, CCM libraries were constructed for cytochrome P450BM3, pfu prolyl oligopeptidase, and the flavin-dependent halogenase RebH. 22–26 sites were targeted for codon mutagenesis in each of these enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Following this report, Lewis and coworkers demonstrated that the E450K mutation in PrnA to improve anthranilic acid activity and selectivity carried over to RebH (E461K) (97). This variant was then used as a starting point for mutagenesis studies that targeted the FAD-binding pocket for improved activity.…”
Section: Structure-guided Mutagenesis Of Fdhsmentioning
confidence: 96%
“…Following this report, Lewis and coworkers demonstrated that the E450K mutation in PrnA to improve anthranilic acid activity and selectivity carried over to RebH (E461K) (97). This variant was then used as a starting point for mutagenesis studies that targeted the FAD-binding pocket for improved activity.…”
Section: Structure-guided Mutagenesis Of Fdhsmentioning
confidence: 96%
“…However, in many applications, 2+ mutations are desired at non-contiguous locations. Recent work has developed a PCR-based method to accomplish this goal in vitro 5 , and we hypothesized that PR was well suited to serve as a complementary approach in vivo , doing away with cloning altogether. To this end, we comprehensively explored the iLOV single mutation sequence-space for thermostability, selected the fitness enhancing mutations, and demonstrated the utility of PR for advanced protein engineering by multiplexing many different single and double mutations at discontinuous sites across iLOV in a second library.…”
Section: Resultsmentioning
confidence: 99%
“…Three RebH variants previously engineered in our laboratory, 1K, 3SS, and 10S, were also fused to RebF through the 16‐residue linker described above. These variants were engineered for altered substrate scope (1K‐E461K+R231K and 3SS‐S2P+M71V+G112S+K145M+N467T+N470S) and site selectivity (10S‐I52H+L380F+F465C+N470S+Q494R+R509Q).…”
Section: Methodsmentioning
confidence: 99%
“…Previously,athermostable flavin reductase from Bacillus subtilis (Fre) was found to be compatible with FDH halogenation systems. [41] This thermostable Fre wast herefore fused to RebH by using the 16-aminoacid linker with the goal of generating af usion enzyme with increased stability.T his resulting fusion enzyme, RebH-16-Fre, also expressed as as oluble protein, but it provided al ower yield for l-tryptophan chlorination (Table 1, entry 5; 30 %y ield), and its melting temperature (apparent T m = 45 8C, Figure S5) was comparable to that of H-16-F. Three RebH variants previously engineered in our laboratory, 1K, [42] 3SS, [16] and 10S, [22] were also fused to RebF through the 16-residue linker described above.T hese variants were engineered for altereds ubstrate scope (1K-E461K + R231K and 3SS-S2P + M71V + G112S + K145M + N467T + N470S)a nd site selectivity (10S-I52H + L380F + F465C + N470S + Q494R + R509Q). Soluble protein was obtained for all FDH fusion enzymes, and bioconversions were conducted with the purified enzymes.A s observed for H-16-F,a ll three FDHf usion enzymes retained activity for their respective substrates (Table 1, entries 7, 9, and 11), but the conversions observed were lower than those of the individual enzymes.B ioconversions using H-16-F,1 K-F,3 SS-F, and 10S-F werescaled up, and the site selectivity of chlorination was found to be the same as that for the corresponding two-component FDH system in all cases (see the Supporting Information and Scheme 2).…”
Section: In Vitro Characterization Of Fdh-fr Fusion Enzymesmentioning
confidence: 99%